A brief overview on the retrofitting possibilities of masonry infill walls - Fangueiro, Raúl (2011)
This work presents a brief review on the seismic behavior on non-loadbearing masonry walls used as masonry infills. O Some examples of inefficient performance are shown based on information available of recent earthquakes. Additionally, a literature overview on the techniques for retrofitting existing masonry infills is provided. Finally, alternative braided reinforced composite materials are briefly described and pointed out as an alternative solution for retrofitting masonry infill walls.